RESEARCH ON THE EVOLUTION AND THE STRUCTURE OF FARMS IN ROMANIA - Mariana BURCEA; Paula STOICEA; Radu Andrei IOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents the evolution and structure of farms in Romania in 2013 in relation to their situation in 2003, but the existing situation in the EU in 2009. The distribution of the agricultural area of farms by size types varies from country to country, and a distinct situation is found in Romania. Research methods used were comparative analysis, absolute and relative deviation from the previous period. The conclusions drawn from this analysis, shows a reduction in the total number of farms in 2013, especially small farms as a result of the comas has, and an increase in holdings with an area of over 10 hectares, thanks the same process. The present situation in Romania causes the creation of subsistence farms, the main form of farm being family type farm.